PENGEMBANGAN MEDIA LEMBAR KERJA SISWA PADA PEMBELAJARAN IPA SEKOLAH DASAR - Mimin Darmini; Khoimatun khoimatun (PGSD Universitas Muhammadiyah Cirebon, 2020)
The existence of learning medium worksheets of students are less effective for teachers in the learning activities then the content is less attractive so that the students ' learning results are declining to the reason for this research to perform. The purpose of this research is to know students ' activities in developing LKS media on elementary School SCIENCE Learning, as well as to learn students ' learning outcomes by developing LKS media. In this study the methods used are research and development. It can be noted that the results of observation of students activities in SCIENCE learning activities are in excellent category (84%), then based on the results of learning analysis of students also increased with N-Gain test (0.50) with moderate criteria. It can be concluded that the development of LKS Learning Media on SCIENCE study was successful because it can increase student activity and student learning outcomes. So it can be a reference for researchers to develop LKS media on other learning Keywords: Student Worksheets Media, SCIENCE Learning, learning outcomes